Kraški pojavi, razkriti med gradnjo slovenskih avtocest - Knez, Martin; Slabe, Tadej (Carsologica, 2007)
Since 1994, karstologists have participated uninterruptedly in the planning and construction of expressways on Slovenia's karst. The choice of expressway and railway routes must above all respect the integrity of the karst landscape and follow recommendations on avoiding major karst surface features and already known caves. Special attention is devoted to the impact of the construction and use of expressways on karst waters. The results of constant research of karst features discovered in the course of the construction of expressways have enriched our knowledge of the natural and cultural heritage and deepened our karstological knowledge. They also represent starting points for planning life on karst surfaces and the protection of karst. The book is intended for karstologists, experts from the field of earth sciences, engineering geologists, planners of traffic routes, students, nature protectionists, planners in administrative units, managers of karst water resources, waterworks, tourist caves, etc.